Implementasi Enkripsi dan Otentikasi Transmisi Data pada ZeroMQ Pipeline Menggunakan Enkripsi AES - I Made Sukarsa; I Made Rama Pradana; Putu Wira Buana (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Communication via sockets is used to transmit information between applications or between processes over network or locally. ZeroMQ is a library for sending messages using sockets that are quite well known. Talking about sending data, message security is an important part that needs to be taken into account, especially when sending data over a network. ZeroMQ sends messages openly without securing the messages sent. This is evidenced by research which states that ZeroMQ does not have a security layer for sending messages over the network and direct observation of message packets using the wireshark application. Therefore, this study creates a method of securing and authenticating message delivery using AES (Advanced Encryption Standard) CBC (Cipher Block Chaining) mode combined with an authentication method. The AES CBC mode was chosen because it is faster than other methods and has strong encryption. This encryption and authentication are used so that the sender and recipient of the message are both valid senders and recipients so that no message changes during message delivery and messages can only be opened by the message recipient and the sender of the message. Tests are conducted to measure the effect of encryption and authentication on message delivery performance. Based on the tests conducted, there is an increase of 7% from normal delivery speed and the potential for messages is not up to 0.3% - 1.5%.